2010
DOI: 10.1097/ico.0b013e31819c4e43
|View full text |Cite
|
Sign up to set email alerts
|

Riboflavin and Ultraviolet A Collagen Crosslinking of the Cornea for the Treatment of Keratitis

Abstract: This case illustrates the positive effects of riboflavin and UV collagen crosslinking on presumed infectious keratitis with a satisfactory final visual outcome. This may be a promising new treatment for keratitis, although this remains to be elucidated in detail in future studies. Until more data are available this treatment should only be considered in therapy-refractive keratitis or ulceration and not in the first line of defence since it may have cytotoxic side effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
64
0
4

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(77 citation statements)
references
References 8 publications
8
64
0
4
Order By: Relevance
“…Moreover, Micelli-Ferrari et al (MicelliFerrari et al, 2009) described a case of keratitis caused by the Gram-negative Escherichia coli treated with CXL with outstanding outcome. Similar results were also reported by More´n et al (More´n et al, 2010), who treated an infectious keratitis using CXL.…”
Section: Corneal Collagen Cross-linking In Infectious Keratitissupporting
confidence: 90%
“…Moreover, Micelli-Ferrari et al (MicelliFerrari et al, 2009) described a case of keratitis caused by the Gram-negative Escherichia coli treated with CXL with outstanding outcome. Similar results were also reported by More´n et al (More´n et al, 2010), who treated an infectious keratitis using CXL.…”
Section: Corneal Collagen Cross-linking In Infectious Keratitissupporting
confidence: 90%
“…Recently, scientists have examined treatment with riboflavin and ultraviolet A light (UVA) in cases of severe infectious keratitis [140,[148][149][150][151]. The mechanism by which this process is thought to work is via collagen crosslinking.…”
Section: Infectious Keratitismentioning
confidence: 99%
“…Studies show that therapeutic transplants represent 2.6% to 17.9% of total penetrating transplants (17) . There are reports of corneal ulcers treated successfully with corneal collagen crosslinking (CXL) (18)(19)(20)(21)(22)(23)(24)(25) . An experimental study found increased resistance to enzymatic digestion by collagenase, pepsin, and trypsin in corneas subjected to CXL (26) .…”
mentioning
confidence: 99%
“…Currently, CXL is usually indicated for cases of keratoconus (30) , pellucid marginal degeneration (31) , painful bullous keratopathy (32) , and iatrogenic ectasia after refractive surgery with laser in situ keratomileusis (LASIK) or photorefractive keratectomy (PRK) (30) . The therapeutic effects of CXL in infectious keratitis are still unclear (18)(19)(20)(21)(22)(23)(24)(25)(26) . This study aimed to evaluate the effect of CXL on infectious keratitis resistant to medical treatment.…”
mentioning
confidence: 99%